Uso de la red social facebook en la población infantil de la parroquia once de Noviembre. - Naranjo Veintimilla, Jenifer Fernanda (2018)
This project is related to the “Use of the Facebook social network at child population of was Once de Noviembre Parish. This problem requires an analysis in depth, but it been studied from the field of communication. The objective is to identify the use of the Facebook social network at second childhood of Once de Noviembre Parish. The applied methodological strategy adheres to a qualitative approach, observation sheet, interviews and focal groups determined the participation of parents and teachers of the Archipiélago de Colón Education Unit, when is concluded that the Facebook social network is a distraction for minors, when they watch videos, images, phrase and play, besides, the children do not know the services that this platform offers in its entirety, on the other hand the parents allow their children to have a Facebook account but in a controlled way, While teachers train their students about the advantages and disadvantages of the social networks in order to use it correctly, the way which they are represented in their profiles is limited, it is pointed out that platform makes the children incorporate different codes to the language and the content they show in their profiles is minimal, for example profiles photo; personal information, due to time restriction. The theoretical contribution to the study is based on authors such as: Almansa, Fonseca & Castillo, 2013 in his article “Using Facebook in Colombia and Spanish youth”. Rodriguez, 2009 in his article “virtual environment in teaching and learning”. Margaix, 2007 in his article “Concepts of web 2.0 and library 2.0: Origin, definitions and challenges for the current libraries.